Beyond simple hetero Diels–Alder cycloadditions. A new type of element–ligand cooperativity at N, C, N-coordinated arsinidene and stibinidene centres in the reaction with an electron-deficient alkyne. Issue 41 (4th October 2022) - Zechovský, Jan; Kremláček, Vít; Erben, Milan; Hejda, Martin; Rychagova, Elena; Jambor, Roman; Růžička, Aleš; Ketkov, Sergey; Dostál, Libor
Abstract : A remarkable activation of the CC triple bond including its stoichiometric hydrogenation was achieved by N, C, N-coordinated pnictinidenes via an element–ligand cooperative mechanism. Abstract : The reactivity of two types of organopnictogen(i ) N, C, N-pincer ligand coordinated compound, i.e. [2, 6-(DippNCH)2 C6 H3 ]E (1-E, where E = As, Sb, Bi; Dipp = 2, 6-iPrC6 H3 ) and [2-(DippNCH)-6-(DippNHCH2 )C6 H3 ]E (6-E, where E = As or Sb), toward an electron-deficient alkyne, i.e. dimethyl acetylenedicarboxylate (DMAD), is reported. All reactions represent remarkable examples of element–ligand cooperation (ELC). In the first step, all compounds react via dearomatization of a latent heteropnictole ring producing rare examples of hetero Diels–Alder (DA) adducts. These compounds then smoothly convert to 1-arsanaphthalenes via hydrogen migration, thereby recovering the aromatic 10π-electron system. Furthermore, in the case of bis(imino) derivatives of 1-E, heating of DA adducts in pyridine led to a hydrogenation of the triple bond of DMAD with the concomitant recovery of the univalent pnictinidene centre, which is in turn able to activate the second molecule of DMAD. In contrast, the non-symmetric derivative of 6-As upon heating in pyridine produced bicyclic trivalent arsenic compounds as a result of an attack of the pendant secondary NH group into the arsa-heterocyclic system. For 6-Sb, a remarkable stoichiometric hydrogenation of the DMAD molecule was observed by NMR spectroscopy involving the reductive elimination of dimethylfumarate in the final step of the reaction sequence. The whole study is accompanied by a theoretical survey that describes the main thermodynamic parameters of the reported reactions and explains the reaction pathways observed in the experiments.